Less basal thyrotropin levels predict antidepressant response in patients with major depression. (1st June 2022) - Navinés, R.; Oriolo, G.; Mora, M.; Cavero, M.; Gómez-Gil, E.; Martin-Santos, R.
Abstract : Introduction: The close association among thyroid metabolism, mood disorders and behavior has long been known. The role of basal thyroid axis in antidepressant treatment response is less known. Objectives: The aim of the present study was to study the association of basal serum thyrotropin (TSH) levels, with antidepressant treatment response in major depressive disorder. Methods: Thirty-one depressed adult outpatients were included. Major depressive episode was diagnosed through the MINI (DSM-IV-TR) interview. Clinical symptomatology and blood samples were assessed at baseline, and at 4- and 8-weeks of either escitalopram or sertraline. Treatment response was defined by an improvement ≥50% in MADRS scores at 4-, and 8-weeks. Basal TSH levels were included in a linear regression model as predictor of treatment response. Results: Twenty-seven patients finished 8-weeks of treatment. Response to treatment was of 74% at 4-weeks, and 63% at 8-weeks of antidepressant treatment. Basal median TSH levels were between normal ranges (M+ SD=1.85+ 1, 02 mlU/L). Basal TSH levels not correlated with basal MADRS scores, but with higher MADRS scores at week-4 (r=0, 415, p=0, 031) and at week-8 (r=0, 392, p=0, 043). Moreover, less baseline TSH levels trend to be a significant good predictor for treatment response at 4-weeks (R 2 =.116, p=.083); and a good predictor at 8-weeks treatment (R 2 =.147, p=.049). Conclusions: Baseline TSH levels even within the normal range may play a role in predicting antidepressant response. Disclosure: No significant relationships.